The correlation between multiple HPV infections and the occurrence, development, and prognosis of cervical cancer - Na, Jing; Li, Ya; Wang, Jun; Wang, Xinyou; Lu, JunLing; Han, Shichao (Frontiers in Microbiology, 2023)
Cervical carcinoma is the fourth female malignant tumor in the world, the persistent infection of high-risk human papillomavirus (HPV) is recognized as the most common cause. This article studies the correlation between multiple HPV infections and occurrence, development, and prognosis of cervical cancer. In order to provide more reference for clinical diagnosis and treatment. We conducted a retrospective analysis of the clinical data of 400 cervical carcinoma patients admitted to our hospital from 2015 to 2023. The collected patient data includes age, HPV infection status, tumor size and morphology, local infiltration depth, diagnostic staging, surgical approach, vascular cancer thrombus status, lymph node status, postoperative HPV follow-up status and so on. We use SPSS statistical software for data analysis. Our research show that the high-risk age group for cervical carcinoma is concentrated between 41 and 60 years old, which is basically consistent with the age range of high incidence of HPV infection. In the statistics of HPV infection types, about 67.7% of patients are single HPV infected, 25.29% are double infected, and 7.00% are infected with three or more types of HPV. Among the multiple HPV infections, the most of patients are under 40 years old and over 70 years old, with double infection accounting for the majority. The top 5 HPV subtypes with high detection rates belong to high-risk subtypes, which are HPV16, 18, 58, 33, and 52 subtypes respectively. There was no significant relationship between multiple HPV infections and cervical cancer stage, lesion size, pathological tissue type, tissue differentiation degree/vascular cancer thrombus and lymph node metastasis, and there was no significant difference in results between the groups.In summary, multiple types of HPV infection in the cervix are common. We found that multiple infections, mainly HPV16 are closely related to cervical cancer. For HPV16.18.58.33.52 subtypes infection, especially for patients under 40 years old and over 70 years old, priority should be given to prevention and treatment. The relationship between multiple HPV infections and the progression and prognosis of cervical carcinoma requires further research, which could better guide cancer prevention and treatment.